Opium use and COVID-19 infection, a retrospective study in Iran - Afshari, Mahdi; Shahramian, Iraj; Salarzaei, Morteza; Mirzaie, Hadi; Parooie, Fateme (Medicni Perspektivi, 2022)
The situation of Covid-19 patients with opium consumption has not been comprehensively investigated especially in Iran. This study is aimed to investigate the effect of current opium addiction on the severity and outcome of the Covid-19 infection. During a retrospective cohort study, clinical, demographic and all variables related to the severity and death due to the Corona virus infection were collected from the medical records of patients hospitalized from February 2020 to June 2021 in the study area. The role of current addiction in the severity and outcome of the disease was investigated using Cox, logistic and linear regression models. Of 939 confirmed Covid-19 cases admitted during the study period, 70 (7.5%) patients were currently addicted. Multivariate regression models showed that current opium addiction significantly increased the chance of endotracheal intubation (OR=2.96, p=0.005) and reduced the mean length of stay in hospital (beta coefficient =-0.42, p<0.0001). However, opium addiction did not change the risk of death (HR= 1.54, p=0.063) or O2 saturation (OR=1, p>0.99). Opium addiction can be associated with the severity of Covid-19 infection, but does not play a considerable role in the mortality of the patients.